Faktor Determinan Pencapaian Imunisasi Dasar Lengkap Pada Bayi - Ponidjan, Tati Setyawati; Tubagus, Putri N.; Sarimin, Dorce Sisfiani; Tamunu, Esther N.; Raule, Jean Henry (POLTEKKES KEMENKES MANADO, 2023)
Background: Complete basic immunization coverage for babies is still a national health problem. According to Basic Health Research (Riskesdas) data, it was found that complete basic immunization coverage in Indonesia in 2018 was still below the national target, including in the city of Tomohon, North Sulawesi Province. Objective: to find out the factors related to achieving complete basic immunization for babies in the working area of ​​the Lansot Health Center in Tomohon City.Method: This research uses design cross sectional 42 respondents, mothers of toddlers aged 1-2 years as research samples, were taken using the technique purposive sampling representing 7 sub-districts in the Lansot Health Center Working Area, Tomohon City. Data was collected using a questionnaire and analyzed using testsChi square. Results : p value The relationship between maternal knowledge and the achievement of complete basic immunization for babies is 0.017 (< 0.05). Meanwhile, the mother's employment factor: is 0.008 (<0.05), the family income factor: is 0.067, and the distance factor for immunization services: is 0.059. This means that there is a relationship between maternal knowledge and occupation in achieving complete basic immunization for babies in the Lansot Community Health Center Working Area, Tomohon City, while family income and distance to immunization services are not related. It is recommended that the Lansot Community Health Center increase education about complete basic immunization for babies in families so that mothers' knowledge can increase and they can also take the time to bring their babies even if the mother works.